Forme di narrazione autobiografica nelle letterature scandinave. Forms of Autobiographical Narration in Scandinavian Literature - Massimo Ciaravolo (Biblioteca di Studi di Filologia Moderna, 2015)
Starting with the great authors of the past, autobiographical requests have been a distinctive feature of Scandinavian literatures. Today, after the modernist experiments of ego building, there is the affirmation of narrative and poetic works which question the boundary between autobiographical truth and fiction, further stimulating the lively, innovative and articulated debate on autobiography in Northern Europe, which has been in development since the 1980s. The 24 authors of the volume (Italian and Scandinavian scholars who are active in Italy or abroad, Scandinavian researchers and writers interested in Italy) illustrate the plurality and uses of autobiographical texts from the 16th century to current days, illuminate areas of a vast territory, investigate little studied texts or go back to questioning the classics.